OTP: an automatized system for managing and processing NGS data - Reisinger, Eva; Eils, Roland (Journal of biotechnology, 2017)
The One Touch Pipeline (OTP) is an automation platform managing Next-Generation Sequencing (NGS) data and calling bioinformatic pipelines for processing these data. OTP handles the complete digital process from import of raw sequence data via alignment of sequencing reads to identify genomic events in an automated and scalable way. Three major goals are pursued: firstly, reduction of human resources required for data management by introducing automated processes. Secondly, reduction of time until the sequences can be analyzed by bioinformatic experts, by executing all operations more reliably and quickly. Thirdly, storing all information in one system with secure web access and search capabilities. From software architecture perspective, OTP is both information center and workflow management system. As a workflow management system, OTP call several NGS pipelines that can easily be adapted and extended according to new requirements. As an information center, it comprises a database for metadata information as well as a structured file system. Based on complete and consistent information, data management and bioinformatic pipelines within OTP are executed automatically with all steps book-kept in a database.